Operation performance evaluation of elevators based on condition monitoring and combination weighting method. (15th May 2022) - Niu, Dapeng; Guo, Lei; Zhao, Weiwei; Li, Hongru
Highlights: A comprehensive evaluation method for the elevator's operation performance is proposed. Through analysis of the elevator's operation mechanism, the elevator's performance evaluation index system is established. By monitoring the elevator's real-time operation information and extracting the signals' time–frequency features, the performance scores of evaluation indexes are calculated. After integrating the objective data and subjective ideas, the combination weighting method is adopted to evaluate the elevators' operation performance level. Abstract: The elevator is an indispensable vertical transportation tool in people's daily life. Its operation performance level is of great importance to the personal safety of passengers. However, elevator performance evaluation is carried out in accordance with some relevant standards and norms at present, and there lacks research on systematic methods for elevator performance evaluation. Therefore, it is of great practical significance and social value to evaluate the performance of elevators. Firstly, this paper establishes an elevator performance evaluation index system by fully analyzing the elevator operation mechanism. The vibration index during elevator operation, the start-stop acceleration index, the noise index, and the door opening and closing speed index are included in the evaluation index system, which can realize a comprehensive performance evaluation of elevators from various aspects. By monitoring the elevator's operation signal and extracting the time–frequency features, the performance scores of each index are calculated based on analysis of information provided by time–frequency feature parameters. In order to avoid the limitations of a single weighting method, a combination weighting method with the maximum deviation squares sum as the optimization objective is adopted to evaluate the operation performance of elevators. Finally, the effectiveness of proposed method is verified through applying to the evaluation of actual elevator systems. In this paper, an evaluation method combining objective data with subjective experiences of experts is proposed and verified through application to evaluation of elevators with different performance levels. The proposed method is expected to be applied to the actual evaluation and maintenance system to play a positive role in guiding the daily maintenance and condition monitoring of elevators.